Phosphate Scavenging During Lava‐Seawater Interaction Offshore of Kīlauea Volcano, Hawaii - Rhea K. Foreman; Karin M. Björkman; Carolina P. Funkey; Nicholas J. Hawco; Samuel T. Wilson; Tully Rohrer; Angelicque E. White; Seth G. John; David M. Karl (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The 2018, subaerial eruption of Kīlauea volcano, Hawaii, resulted in a 5‐km‐long stretch of coastline that actively drained lava into the ocean. Nutrients were added to the surrounding ocean through the dissolution of basaltic rock and thermal upwelling of deep water, thereby fueling a large phytoplankton bloom. Lava‐impacted, surface seawater had high suspended particle loads, and concentrations of chlorophyll, silicic acid, phosphate (Pi), nitrate, and iron that were elevated up to 12, 36, 5, 960, and 1,400 times, respectively, above the background oligotrophic levels. Widespread precipitation of iron oxyhydroxides (Feox) led to extensive scavenging of the dissolved Pi pool, similar to what occurs along mid‐ocean ridge hydrothermal systems. This scavenging transformed a “fertilization” event into a Pi sink near the coast of the ocean entry; however, nutrient data from outside the bloom suggest that Pi could also desorb from the Feox as it is dispersed into the open ocean. From lava quench experiments, we estimate that the hydration state of the Feox precipitate (H2O/Fe) was 5.2–5.7, and that the equilibrium partition coefficient of Pi into Feox (solid/liquid) was 106. In addition, 33Pi radiotracer incubations were used to differentiate between biotic and abiotic uptake of Pi at Kīlauea's ocean entry. These findings are important for understanding modern‐day volcanic fertilization events, modeling nutrient dynamics during major events in Earth history (such as oxygenation of the atmosphere and the formation of large igneous provinces), and predicting the marine response to greater continental weathering in a warming climate.